Big sky country eaudiobook Parable, montana series, book 1. - Miller, Linda Lael (Parable, Montana, 2012)
New York Times best-selling author Linda Lael Miller has earned a large and growing following for her wildly popular novels starring the Creeds and McKettricks. As her many fans will attest, no one brings cowboys-and their affairs of the heart-to life in quite the way she does. With the author's signature style, Big Sky Country delivers a scintillating tale that Miller's many fans will not want to miss.